Effect of Dietary Supplementation of Tootache Plant (Acmella oleracea) Extract on the Growth Performance of Cirrhinus mrigala Fingerlings - Ngilyang Moda; M.K Yadav; Shriparna Saxena; Deepak Kher (Archives of Current Research International, 2025)
This study investigated the efficacy of Acmella oleracea extract on the growth performance of Cirrhinus mrigala fingerlings. This trial was designed for 45 days. The experiments were designed as T0 (0%) T1 (0.5%), T2 (1.0%), and T3 (1.5%) A. oleracea extract with three replications. During the study the growth parameters including net weight gain, percent weight gain, length gain, specific growth rate and feed conversion ratio were recorded at 15-days interval. Results indicated a significant improvement (p < 0.05) in growth parameters in all treated groups compared to the control, with the best performance was observed at the T1 treatment. Fish fed with 0.5 percent A. oleracea extract exhibited the highest net weight gain (32.3 ± 1.15 g), percent weight gain (61.64% ± 1.36), specific growth rate (1.067% ± 0.018), and the most efficient feed conversion ratio (2.62 ± 0.049). Higher concentrations (T2 and T3) showed moderate improvements but were less effective than the T1 treatment, suggesting a dose-dependent response. This study highlights the potential of A. oleracea as a natural, cost-effective, and sustainable growth promoter in aquafeed.